RFID TECHNOLOGY: AN OVERVIEW - Pal, Amit; Tripathi, Akanksha; Saigal, Anupam (International Journal of Research -GRANTHAALAYAH, 2017)
The information technology has changed the way library professional to interact, communicate, share and acquire knowledge. However, when the computer was created it did not have features and facilities for users to interact. With the evaluation of Internet and Communication Technology, manual library has evolved into a dynamic, interactive and collaborative platform that facilitates exchange of knowledge and information among its users. RFID is the latest technology to be used in libraries and information centers for book identification, for self-checkout and for theft detection. This paper presents an overview of RFID, it defines RFID, Components, Benefits and Limitations.